Analisis Beban Penyusutan Aktiva Tetap Dan Pengaruhnya Terhadap Pajak Penghasilan Badan Pada PT Eka Plafindo Jaya Medan - Diana Afriani; Denny Salim; Stefvy Stefvy (CV. ITTC INDONESIA, 2025)
The purpose of this research is to know the impact of implementation of fixed asset depreciation according to income tax provision to entity income tax in PT Eka Plafindo Jaya Medan. Types of this research is in form of descriptive research with case study in PT Eka Plafindo Jaya Medan. Data which is collected is secondary data include the the depreciation calculation, entity income tax calculation, presentation of financial statement in year 2023 and other information which is related with this research. The research result shows that fixed asset depreciaton method according to income tax provision has impact in increasing of entity’s income tax at PT Eka Plafindo Jaya Medan in year 2023. There is difference between commercial depreciation expense and fiscal depreciation expense because there is difference in using of depreciation method. The company implements straight line method in calculating depreciation expense. The group of fixed asset is not determined properly by the company. The company does not conduct fiscal correction on difference between commercial depreciation expense and fiscal depreciation expense. The company does not calculates the depreciation expense of building, vehicle and furniture properly according to income tax provision. There is improper depreciation rate of fixed asset on building, vehicle and furniture. The depreciation expense in the company is Rp 823,500,000.00. The depreciation expense based on income tax provision is Rp 572,375,000.00. The company should conduct fiscal correction in amount of Rp 251,125,000.00. The fiscal correction will increase the taxable income in amount of Rp 251,125,000.00. The entity income tax in company is Rp 698,748,750.00. After implementation of depreciation of fixed asset based on income tax provision, the entity income tax expense is Rp 761,530,000.00.